Penerapan Model Discovery Terbimbing Pada Pembelajaran Geografi Untuk Meningkatkan Hasil Belajar Siswa Kelas X di SMA Negeri 5 Toraja Utara - Panggalo, Irra; Andaria, Kalvin Salindeho; Rifani, Irfan (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
This research aims to determine the effect of implementing the guided discovery model on class X geography learning at SMA Negeri 5 Toraja Utara. The research method used is a quantitative method. The research location is at SMA Negeri 5 Toraja Utara. Data collection techniques are observation, tests and documentation. The population in the research is class X with a total of 96 students and the sample is 20 people. The data analysis technique used is descriptive and inferential statistical analysis. The results of the research show that the value of tcal is 12.98 and ttable is 2.10092, tcal>ttable= 12.98 >2.10092. At the Sig ÃŽÂ± level there is a test of 2 variables with the result at t0.05 value ttable= 2.10092, so it can be concluded that H0 is rejected and H1 is accepted, which means that the guided discovery model has a positive influence in improving the geography result at SMA Negeri 5 Toraja Utara.